Evolutionary conserved regulation of TFEB stability by the E3 ubiquitin ligase WWP2 modulates response to stress in vivo - Juan A. Garcia-Sanchez; Estelle Bonnet; Céline Loubatier; Anne Doye; Guillaume Paillier; Fabien Segui; Frédéric Larbret; Paul Chaintreuil; Ludovic Batistic; Cédric Torre; Marcel Deckert; Jolanta Polanowska; et al. (iScience)
Summary: Transcription factor EB (TFEB) is a key transcription factor that orchestrates the cellular response to stress. Dysregulation of TFEB is associated with a range of human diseases, and understanding the regulatory mechanisms of TFEB is crucial for identifying potential drug targets. In this study, we used Caenorhabditis elegans to screen for E3 ubiquitin ligases regulating the activity of TFEB’s homolog, HLH-30, upon pathogenic infection. We identified WWP-1 as a regulator of HLH-30-dependent immune response controlling HLH-30 stability to mediate host defense in vivo. We found that HLH-30 interacts with WWP-1, supporting a model of WWP-1 directly regulating HLH-30. Furthermore, we found that WWP-1’s human homolog WWP2 binds TFEB, directly induces TFEB ubiquitination and stabilizes TFEB. Finally, we found that WWP2 is required for TFEB-dependent host response in human monocytes-derived macrophages upon infection. Overall, our work has identified an evolutionarily conserved regulation of TFEB by WWP2 and highlighted its role in modulating stress response.